A Dual Role of Cyclin E in Cell Proliferation and Apotosis May Provide a Target for Cancer Therapy - Mazumder, S.; DuPree, E. L.; Almasan, A. (Current Cancer Drug Targets, 2004)
Cyclin E is essential for progression through the G1-phase of the cell cycle and initiation of DNA replication by interacting with and activating its catalytic partner, the cyclin dependent kinase 2 (Cdk2). Rb, as well as Cdc6, NPAT, and nucleophosmin, critical components of cell proliferation and DNA replication, respectively, are targets of Cyclin E / Cdk2 phosphorylation. There are a number of putative binding sites for E2F in the cyclin E promoter region, suggesting an E2F-dependent regulation. Skp2 and Fbw7 are novel proteins, responsible for ubiquitin-dependent proteolysis of Cyclin E. The tight regulation of cyclin E expression, both at the transcriptional level and by ubiquitin-mediated proteolysis, indicates that it has a major role in the control of the G1- and S-phase transitions. Cyclin E is also transcriptionally regulated during radiation-induced apoptosis of hematopoietic cells. In addition to its biological roles, deregulated cyclin E expression has an established role in tumorigenesis. Cell cycle regulatory molecules, such as cyclin E, are frequently deregulated in different types of cancers, where overexpressed native or low molecular weight forms of Cyclin E have a significant role in oncogenesis. During apoptosis of hematopoietic cells, caspase-dependent proteolysis of Cyclin E generates a p18-Cyclin E variant. Understanding the role of Cyclin E in apoptosis may provide a novel target, which may be effective in cancer therapy. This review summarizes what is known about the biological role of cyclin E, its deregulation in cancer, and the opportunities it may provide as a target in clinical therapy.
Keywords: phosphorylation